The application of PLS & SEM in determining the antecedents of supplier-manufacturer relationship - Hassan, Mohamad Ghozali; Abdul Talib, Asmat Nizam; Harun, Noor Aziani; Johari, Nor Azmi (IACSIT Press, Singapore., 2012)
The purpose of this study was to examine the antecedent to supplier-manufacturer relationship.There are three dimensions of antecedents of a relational-oriented exchange which are dependence, trust, and communication behavior that has been measured the impact on strategic relationship. This study used the partial least squares (PLS) and structural equation modeling (SEM) tool to test the hypotheses.The result indicated that dependence and communication behavior were positively related to the strategic relationship.This study also found that communication behavior was the most significant predictor of extent of strategic relationship followed by dependence.